Catching Up: The Role of State Science and Technology Policy in Open Innovation. - Mayer, Heike (Economic Development Quarterly, 2010)
This article examines the impact of the emerging model of open innovation on state public policy, particularly the practice of technology-based economic development in weak research and development (R&D) states. Open innovation describes the nascent practice of firms using knowledge created outside their boundaries and also marketing ideas they would not commercialize themselves. Firms engaging in open innovation thrive on knowledge spillovers, and weak R&D regions could benefit from this model through the creation of Marshallian externalities. It is therefore interesting to ask whether weak R&D states take advantage of this model. This case study analysis shows that states involved in the Experimental Program to Stimulate Competitive Research partially support the emerging open innovation paradigm. All states have science and technology strategies and actively support and invest in their higher education infrastructure. They show variation in their support for university–industry partnerships, entrepreneurship, capital access, commercialization, and technology transfer. None of the states, however, uses the open innovation framework explicitly.